Can industrial diversification help strengthen regional economic resilience? - He, Dan; Miao, Pengjia; Qureshi, Naveed Akhtar (Frontiers in Environmental Science, 2022)
Strengthening economic resilience is the key to stable economic growth in various regions. Previous studies have paid more attention to the level and evolution trend of economic resilience, and seldom Dissected the reasons for differences in regional economic resilience. This paper takes 243 cities in China as the research object and explains the reasons for the differences in regional economic resilience from the perspective of industrial diversification. The results show that industrial diversification helps to improve the level of regional economic resilience. Compared with related diversification, unrelevant diversification has a more significant effect on economic resilience. The region’s own endowment conditions will also affect the effect of industrial diversification on economic resilience. Diversified industries can better promote regional economic resilience in more economically developed cities. The development of industrial diversification also depends on the support of external factors such as finance, technological innovation, and human capital. Therefore, increasing the investment in these factors will also help to positively adjust the role of industrial diversification in promoting economic resilience. Our research helps to understand the reasons for the formation of regional economic resilience, and the research results provide a scientific basis for optimizing sustainable development policies.